2000
DOI: 10.1063/1.371938
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved ultraviolet photoelectron spectroscopy of In-[perylene-3,4,9,10-tetracarboxylic dianhydride] system

Abstract: The In-[perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA)] system, obtained by the sequential evaporation of PTCDA and In on cleaved MoS2 surfaces, was measured by means of angle-resolved ultraviolet photoelectron spectroscopy. The results indicate that the four In atoms react with one PTCDA molecule. Using a model compound of the reaction product, In4PTCDA, the quantitative analysis of the take-off angle (θ) dependence of the photoelectron intensity from the new band shows that the band originates from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…It is likely, therefore, that the PTCDA molecules interact with surface In atoms. It is interesting to note that previous studies have shown that an interfacial interaction occurs when In is deposited onto PTCDA films, with charge transferred from the In atoms to the C atoms of the carboxylic groups [25,26]. While the HREELS results obtained for PTCDA/InSb(1 1 1)A appear to confirm the Note that each spectrum is normalised to the maximum intensity in the 1300-2300 cm À1 range for ease of comparison.…”
Section: Hreelssupporting
confidence: 67%
“…It is likely, therefore, that the PTCDA molecules interact with surface In atoms. It is interesting to note that previous studies have shown that an interfacial interaction occurs when In is deposited onto PTCDA films, with charge transferred from the In atoms to the C atoms of the carboxylic groups [25,26]. While the HREELS results obtained for PTCDA/InSb(1 1 1)A appear to confirm the Note that each spectrum is normalised to the maximum intensity in the 1300-2300 cm À1 range for ease of comparison.…”
Section: Hreelssupporting
confidence: 67%
“…In a previous ARUPS study, 4 we showed that by the reaction with In atoms flat lying PTCDA molecules on MoS 2 become tilted; the averaged tilt angle was determined as ap- proximately 10°, slightly different from the present value, probably because no heat treatment was performed for the reported ARUPS sample 4 and therefore the In-PTCDA reaction was not complete. In our recent ARUPS measurements we found that for the In-PTCDA/MoS 2 system obtained after heat treatment the take-off angular dependence of the photoelectrons from the highest occupied molecular orbital was broader than for the system without heat treatment and gave a better agreement with the calculated one for the molecules with the above described tilt angle.…”
Section: Resultscontrasting
confidence: 76%
“…3 Recently we performed angle-resolved ultraviolet photoelectron spectroscopy ͑ARUPS͒ studies with synchrotron radiation for the In-PTCDA/MoS 2 system, obtained by sequential evaporation of PTCDA and In on a cleaved MoS 2 surface, to study the origin of the band-gap state appearing at the In/PTCDA interface. 4 Kera et al studied the valence band structure of the similar system by metastable atom electron spectroscopy ͑MAES͒. 5 From these studies, it was concluded that ͑i͒ the band-gap state can be well explained by the calculated energy level for a model In-PTCDA reaction product, In 4 PTCDA, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In these spectra, the photoelectrons from the substrate are negligible, because the spectra show little film thickness dependence for the thickness up to 44 Å. The photoelectrons from the first 2–4 Å contribute to the spectra . Before the samples are exposed to air, the NbO 2 is predominant on the outermost of the film.…”
Section: Resultsmentioning
confidence: 99%